Bilateral segmental aplasia of oviduct with secondary hydrosalpinx in a buffalo - KUMARESAN, A; ANSARI, M R (The Indian Journal of Animal Reproduction, 2023)
The present paper reports an interesting case of bilateral segmental aplasia of oviduct along with hydrosalphinx and extensive ovarian adhesion in a buffalo.